Literature and religious culture in seventeenth-century England - Barbour, Reid (Cambridge University, 2013)
Reid Barbour's study takes a fresh look at English Protestant culture in the reign of Charles I (1625-1649). In the decades leading to the civil war and the execution of their monarch, English writers explored the experience of a Protestant life of holiness, looking at it in terms of heroic endeavors, worship, the social order, and the cosmos. Barbour examines sermons and theological treatises to argue that Caroline religious culture comprised a rich and extensive stocktaking of the conditions in which Protestantism was celebrated, undercut, and experienced. Barbour argues that this stocktaking was also carried out in unusual and sometimes quite secular contexts: in the masques, plays, and poetry of the era as well as in scientific works and diaries. This broad-ranging study offers an extensive reappraisal of crucial seventeenth-century themes, and will be of interest to historians as well as literary scholars of the period.